2012
DOI: 10.1007/s11538-011-9712-y
|View full text |Cite
|
Sign up to set email alerts
|

A Fibrocontractive Mechanochemical Model of Dermal Wound Closure Incorporating Realistic Growth Factor Kinetics

Abstract: Fibroblasts and their activated phenotype, myofibroblasts, are the primary cell types involved in the contraction associated with dermal wound healing. Recent experimental evidence indicates that the transformation from fibroblasts to myofibroblasts involves two distinct processes: The cells are stimulated to change phenotype by the combined actions of transforming growth factor β (TGFβ) and mechanical tension. This observation indicates a need for a detailed exploration of the effect of the strong interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 89 publications
1
46
0
Order By: Relevance
“…Similar to Olsen et al (1995), we assume that the rate of cell differentiation is dependent on the concentration of the signaling molecule with no cell differentiation taking place in the absence of this signaling molecule. Like others such as Javierre et al (2009), Murphy et al (2012), and Valero et al (2014a; b), we are aware of the fact that this cell differentiation can only take place under conditions of sufficient mechanical stiffness. It seems like a good idea then to incorporate this phenomenon also into the model.…”
Section: Discussionsupporting
confidence: 54%
“…Similar to Olsen et al (1995), we assume that the rate of cell differentiation is dependent on the concentration of the signaling molecule with no cell differentiation taking place in the absence of this signaling molecule. Like others such as Javierre et al (2009), Murphy et al (2012), and Valero et al (2014a; b), we are aware of the fact that this cell differentiation can only take place under conditions of sufficient mechanical stiffness. It seems like a good idea then to incorporate this phenomenon also into the model.…”
Section: Discussionsupporting
confidence: 54%
“…As the collagen density increases, the tissue becomes stiffer [29], regulating the volumetric strain of the tissue , which in turn defines the value of and the stresses exerted by the cells on the ECM. We consider also that depends on the concentration of fibroblasts and myofibroblasts, with a term similar to the one proposed by Murphy et al [25]. Contractile forces exerted by fibroblasts can initiate wound closure and myofibroblasts are known to contribute to the transmission of these contraction forces [29], [30].…”
Section: Resultsmentioning
confidence: 99%
“…Adam [18] investigated the occurrence of non-healing wounds and the so-called critical size defect with a simple model that describes the evolution of a generic growth factor activating cell proliferation at the wound edge. Olsen's model [21] has been recently revised by different authors [23][25]. These works incorporate the decreased mechanical properties of the granulation tissue and combine for the first time the coupled actions of chemical and mechanical factors on the fibroblast to induce myofibroblast differentiation, although the studies differ in the mechanical stimulus used to drive the differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this investigation, we assume that this conversion occurs rapidly, and we represent both active and latent forms of TGF-b by a single species, b. Fibroblasts are one of the main sources of TGF-b in wounds [48], and their production of this GF is inhibited if TGF-b is already present [25]. We model this production using a saturation form, in line with the work of Murphy et al [23], with the constant l 21 characterizing the rate of production by fibroblasts and the constant l 23 characterizing the half-maximal rate of production. It has been observed that this production by fibroblasts is downregulated by the presence of keratinocytes [68], and we model this using a downregulatory coefficient l 22 .…”
Section: Mathematical Modelmentioning
confidence: 99%